Conventional Controller Design for the Reactor Power Control System of the Advanced Small Pressurized Water Reactor. (3rd April 2017) - Wan, Jiashuang; Wang, Pengfei; Wu, Shifa; Zhao, Fuyu
Abstract: The objective of this paper is to design a reactor power control system for the advanced small pressurized water reactor that adopts a constant average coolant temperature and a secondary-side steam pressure program. Based on the nonlinear core model with the one-group delayed neutron and simplified nonlinear once-through steam generator model, a two-input and two-output linear nuclear steam supply system (NSSS) model is obtained. Three types of control systems are then proposed and designed on a Bode diagram using analytical methods and second-order approximation. The comparison of the control performance and robustness of the three control systems shows that the double feedback control (DFC) with both power feedback and temperature feedback provides the best performance for reactor power and average coolant temperature with parameter uncertainty due to control rod differential worth variation. The simulations based on the high-order nonlinear NSSS model also show good performance of the DFC system.